The mathematics of banking and finance - Cox, Dennis W. 4 0 16; Cox, Michael A. A.; 5 (Chichester, England ;;Hoboken, NJ : Wiley, 2006)
Throughout banking, mathematical techniques are used. Some of these are within software products or models; mathematicians use others to analyse data. The current literature on the subject is either very basic or very advanced. The Mathematics of Banking offers an intermediate guide to the various techniques used in the industry, and a consideration of how each one should be approached. Written in a practical style, it will enable readers to quickly appreciate the purpose of the techniques and, through illustrations, see how they can be applied in practice. Coverage is extensive and includes techniques such as VaR analysis, Monte Carlo simulation, extreme value theory, variance and many others. A practical review of mathematical techniques needed in banking which does not expect a high level of mathematical competence from the reader
Includes index.
Keywords: 2 -- 0; 6; Mathematics.;Mathematical models. -- Business mathematics.;Banks and banking;Finance -- 20; 20; 2